Mechanism of ferrite grain refinement in the (γ + α) region of weathering steel Cu–P–Cr–Ni–Mo. Issue 16 (28th August 2015) - Zhang, Chunling; Zhang, Mengmeng; Guo, Tengteng; Yang, Jinfeng; Kong, Yuting; Cai, Dayong; Li, Qiang
Abstract: Abstract : In this study, the mechanism of ferrite grain refinement during warm compression deformation in the (γ + α) region of Cu–P–Cr–Ni–Mo weathering steel was analyzed by optical microscopy and electron backscatter diffraction. Results showed that fine equiaxed ferrite grains surrounded by high-angle boundaries (HABs) formed along the initial boundaries as the strain is increased. As the deformation temperature decreased, some low-angle boundaries shifted to HABs in intragranular ferrite, and ferrite grain refinement was promoted by continuous dynamic recrystallization. Microstructural observations also indicated that the fine ferrite grains of approximately 1.4–3 μm in size can be obtained by deformation at 750 °C with a strain over 0.69 because of ferrite dynamic recrystallization. Moreover, both strain and deformation temperature influenced the ferrite grain size and volume fraction. Thus, the predominant mechanism for ferrite grain refinement in the (γ + α) region was continuous dynamic recrystallization.